Hadith in the Context of Globalization: Opportunities and Challenges - Solihin Ma’ruf; Tata Setiana; Muhammad Al Mighwar; Engkos Kosasih; Irwan Abdurrahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Globalization has brought significant changes in various aspects of life, including religious understanding and practice. This study discusses the position and role of Hadith in facing the challenges and opportunities arising from the current of globalization. Through a qualitative approach with literature analysis, this research identifies that the context of Hadith in the globalization era is related to two aspects: the development of Hadith studies from time to time up to the current development through digital technology and social media, and its application in facing the era of globalization. The results of the study indicate that to deal with these challenges and opportunities, the critical study approach to understanding Hadith through the utilization of technology must refer wisely and prudently to the methodological concepts formulated by previous scholars (ulama terdahulu) in order to support the strengthening of Hadith's authenticity. Furthermore, Hadith, with the development of its studies and applications exemplified by the ulama mutaqaddimin (earlier scholars) and muta'akhkhirīn (later scholars), remains always relevant to the progress of the times.